1978
DOI: 10.1152/ajpregu.1978.235.1.r76
|View full text |Cite
|
Sign up to set email alerts
|

Actions of some transmitters and their antagonists on salivary secretion in a tick

Abstract: Cholinomimetics (pilocarpine, carbachol, physostigmine, acetylcholine, acetyl-beta-methylcholine) and sympathomimetics (dopamine, epinephrine), when injected into the hemolymph, provoked salivary fluid secretion in the female ixodid tick Amblyomma hebraeum Koch. Atropine, but not tubocurarine or toxiferine, abolished pilocarpine-induced secretion without reducing the response to dopamine. Reserpine and guanethidine likewise selectively attenuated pilocarpine-induced secretion. Following extirpation of the syng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 0 publications
1
47
2
Order By: Relevance
“…In ixodid salivary glands, MIP and SIFamide probably regulate dopamine secretion from the basal acinar cells of acini II and III into the acinar lumen, where dopamine then binds to the dopamine D1 receptor to stimulate secretion of secretory granules (Šimo et al 2014, 2012, 2011, 2009b). In this regard, injection of argasids and ixodids with cholinergic stimulants, such as pilocarpine and carbachol induces salivation (Howell, 1966;Kaufman, 1978;Tatchell, 1967a). Cholinergic stimulants do not act on isolated salivary glands of hard or soft ticks (Kaufman, 1978;Mans, 2002;Maritz-Olivier, 2005), suggesting that they act on the central nervous system, whereas stimulation of isolated argasid and ixodid salivary glands with dopamine induces secretion (Kaufman, 1977;Mans, 2002;Maritz-Olivier, 2005).…”
Section: The Arthropod Nervous System and Salivary Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ixodid salivary glands, MIP and SIFamide probably regulate dopamine secretion from the basal acinar cells of acini II and III into the acinar lumen, where dopamine then binds to the dopamine D1 receptor to stimulate secretion of secretory granules (Šimo et al 2014, 2012, 2011, 2009b). In this regard, injection of argasids and ixodids with cholinergic stimulants, such as pilocarpine and carbachol induces salivation (Howell, 1966;Kaufman, 1978;Tatchell, 1967a). Cholinergic stimulants do not act on isolated salivary glands of hard or soft ticks (Kaufman, 1978;Mans, 2002;Maritz-Olivier, 2005), suggesting that they act on the central nervous system, whereas stimulation of isolated argasid and ixodid salivary glands with dopamine induces secretion (Kaufman, 1977;Mans, 2002;Maritz-Olivier, 2005).…”
Section: The Arthropod Nervous System and Salivary Secretionmentioning
confidence: 99%
“…In this regard, injection of argasids and ixodids with cholinergic stimulants, such as pilocarpine and carbachol induces salivation (Howell, 1966;Kaufman, 1978;Tatchell, 1967a). Cholinergic stimulants do not act on isolated salivary glands of hard or soft ticks (Kaufman, 1978;Mans, 2002;Maritz-Olivier, 2005), suggesting that they act on the central nervous system, whereas stimulation of isolated argasid and ixodid salivary glands with dopamine induces secretion (Kaufman, 1977;Mans, 2002;Maritz-Olivier, 2005). Sequence homologs for the receptor for SIFamide (sifa-r) have been detected in salivary gland transcriptomes of ixodid and argasid ticks, suggesting that the SIFamide-dopamine system may be conserved in all ticks (Egekwu et al 2016;Šimo et al 2013; B.J.…”
Section: The Arthropod Nervous System and Salivary Secretionmentioning
confidence: 99%
“…Five microliters of a 10 -3 M solution of dopamine, 6-hydroxydopamine (6-OHdopamine) (as the hydrochloride), cyclic AMP, acetylcholine, pilocarpine, serotonin, reserpine (Sigma Chemical Co., St. Louis, Missouri) or DL-c~-methyl-m-tyrosine methyl ester hydrochloride (98 % pure, MTME, a gift from E Papavasiliou, Veterans Hospital, Hampton, Virginia) was administered to D. variabilis females. Ticks apparently tolerate these dosages, which exceed typical physiological concentrations, as demonstrated by Kaufman (1978).…”
Section: Methodsmentioning
confidence: 93%
“…Although there have been many investigations on the effects of adrenergic and cholinergic agonists on the release of amylase and K+ from the salivary glands of several species (VREUGDENHIL and ROUKEMA, 1975;BOGART and PICARELLI, 1978;KAUFMAN, 1978;KAUFMAN and WONG, 1983), the reports in which the release of sialic acid from the salivary gland is studied are few. DOUGLAS and PoISNER (1964) and SAMLI and GESCHWIND (1968) reported that high K} concentrations in the medium provoked the release of vasopressin and luteinizing hormone from pituitary gland.…”
Section: Discussionmentioning
confidence: 99%